CAT25 defines microsatellite instability in colorectal cancer by high-resolution melting PCR. Issue 3 (2nd July 2020) - Sánchez, AG; Juaneda, I; Eynard, H; Basquiera, AL; Palazzo, E; Calafat, P; Palla, V; Romagnoli, PA; Alvarellos, T
ABSTRACT: Background: CAT25 (T25 mononucleotide repeat of the Caspase 2 gene), is a promising DNA marker for detecting microsatellite instability (MSI) in colorectal cancer. CAT25 has the potential to be incorporated into the Bethesda panel, a commonly used panel of DNA microsatellites, or replace it in its entirety. We aimed to develop and validate a high-resolution melting-PCR (HRM-PCR) method for CAT25 instability detection in clinical samples. Methods: The instability of CAT25, BAT25 (a poly(A) tract occurring in c‐kit ) and BAT26 (a poly(A) tract localized in hMSH2 ) microsatellites were assessed in DNA from tumour and peripheral blood obtained from 110 patients with colorectal cancer using HRM-PCR and capillary electrophoresis. Immunohistochemistry (IHC) staining for MSH2, MSH6, MLH1, and PMS2 enzymes was performed on tumours with jigj MSI. Allelic size variation of CAT25 was analysed on peripheral blood DNA from 208 healthy volunteers. Results: The HRM-PCR for CAT25 was validated in clinical samples. CAT25 showed a tight range of 64–66 base pairs. Of 110 tumours, 11 had High MSI, later confirmed by IHC. CAT25 defines MSI alone as well as when used together with BAT25 and BAT26. CAT25 results provided 100% predictive values and p < 0.0001 to classify a tumour as having high MSI. Conclusions: We developed and validated a new HRM-PCR assay to detect CAT25 instability. Our findings showed a limited allelic size variation of CAT25 and highlighted to CAT25 as a promising marker for MSI analysis.